Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility(CSR) Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI) - Hanum, Latifah; Indra Azra, Fefri; Areva, Desi (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This research has a background by needCorporate Social Responsibility as logical consequences, which itâs principleÂ explain a corporation mush keep mind on stakeholders as soon asÂ Â loyalty and corporate value. The research aims to know any contribution of good corporate governance and corporate social responsibility as moderate variable tocorporate value, on manufacturing enterprise, whichregistered in Indonesiaâs Busary Effect(BEI). The research use Moderated Regresion Analysis (MRA). Based on result of analyze data got GoodCorporate Governance have significant contributetocorporate value on manufacturing enterprise, registered in Indonesiaâs Busary Effect (BEI). Corporate Social Rsesponsibilityhave significant contributetocorporate value on manufacturing enterprise, registered in Indonesiaâs Busary Effect (BEI).Good Corporate Governance, moderated Corporate Social Responsibilityhave notÂ significant contributetocorporate value on manufacturing enterprise, registered in Indonesiaâs Busary Effect (BEI). And Good Corporate Governance dan Corporate Social Responsibilityhave simultaneously significant contributetocorporate value on manufacturing enterprise, registered in Indonesiaâs Busary Effect (BEI).